EFFECTS OF PREBIOTICS ON METABOLIC ACTIVITY IN BROILERS - NAWAZ , A; USMAN , M; ALI , MM; AHMAD , A; JAHANGIR , M; ŞAHIN , T; IQBAL , R; KHAN , AMA; WAHEED , SF; SARMAD , M (Biological and Clinical Sciences Research Journal, 2024)
The present study will aim to assess the effects of prebiotic supplementation on growth performance, protein metabolism, and gut health in broiler chickens using mannan-oligosaccharides (MOS) as a model prebiotic. The purpose is to determine if prebiotics will be beneficial alternatives for antibiotic growth promoters in improving the flock performance and meeting quality-related parameters in broilers. A 42-day randomized controlled trial on one-day-old Ross 308 broiler chicks will be divided into four groups: Control, Inulin (IN), MOS, and FOS. The study shall determine Body Weight Gain (BWG), Feed Intake (FI), Feed Conversion Ratio (FCR), Protein Digestibility, Lipid content, & Gut Microbiota composition using 16S rRNA sequencing. Anticipated criteria include improvement in body weight gain (BWG), feed conversion ratio (FCR), protein digestibility, and beneficial modulation of gut microbiota composition at successively higher pricing than the control group, which are shown as MOS. The study will also record a decrease in saturated fatty acids and an increase in polyunsaturated fatty acids in the breast muscle, which indicates improved meat quality. These results will add to the literature that provides evidence for using prebiotics as a natural substitution in poultry nutrition due to its benefits. The research results will highlight the possibility of using MOS as an alternative to antibiotics in broiler diets and their effect on growth performance (with meat quality) and gut health. Nonetheless, the limitations of the short study duration and only using one broiler strain will be noted, with suggestions to replicate these findings over extended periods in more strains to validate prebiotics in poultry nutrition.